Empirical validation and comparison of PCM modeling algorithms commonly used in building energy and hygrothermal software. (15th April 2020) - Wijesuriya, Sajith; Tabares-Velasco, Paulo Cesar; Biswas, Kaushik; Heim, Dariusz
Abstract: Whole building energy modeling has become extremely important for designers, architects, engineers, and researchers to predict energy performance of buildings. This is particularly important for phase change materials (PCMs) due to their variable properties. For this reason, building energy modeling tools have been developed and validated against different sources of experimental data. However, an IEA Annex 23 surveyed over 250 research publications concluding that the general confidence in currently used numerical models is still too low to use them for designing and code purposes. The objective of this study is to assess the capability of different simulation programs to model the PCMs in building envelope using data from two independent studies using Nano-encapsulated PCMs (Nano-PCM) and shape-stabilized PCMs. The study finds that the investigated PCM models accurately predict the PCM behavior in the building envelope. Highlights: Validation study considered 6 PCM models in 5 software packages. Two independent experimental studies provide the data. Studies use Nano-PCM embedded in drywall and shape-stabilized PCM behind drywall. Comparison of the modeled results demonstrate their ability to accurately model PCMs.